PENGEMBANGAN REST API UNTUK INFORMASI PASAR TRADISIONAL DI KOTA YOGYAKARTA DENGAN METODE INCREMENTAL - Agata Filiana; Maria Nila Anggia Rini; Andhika Galuh Prabawati; Rindho Ananta Samat (SINTECH (Science and Information Technology) Journal, 2022)
Traditional markets in the city of Yogyakarta offer many unique things for both locals and tourists. There has yet to be an effort to centralise information on traditional markets which highlights its characteristics, including its uniqueness. Through this study, we designed a REST API that provides a service to access information on traditional markets in the city of Yogyakarta. The information available includes class, alternative names, location, description, history, facts, facilities, uniqueness, photos, and stalls. This service can be used by governments or other parties through external applications ensuring data accuracy. We used an incremental approach made of three iterations. Each iteration consisted of needs analysis, system design, API development, and testing and evaluation. This approach provided a more focused and targeted development based on the functional needs of each iteration. Each iteration was tested both on Postman and a web application. The result of this REST API is a JavaScript Object Notation (JSON) which can be easily processed by external applications.